2001
DOI: 10.1186/1471-2164-2-11
|View full text |Cite
|
Sign up to set email alerts
|

Gene conversion homogenizes the CMT1A paralogous repeats

Abstract: Background: Non-allelic homologous recombination between paralogous repeats is increasingly being recognized as a major mechanism causing both pathogenic microdeletions and duplications, and structural polymorphism in the human genome. It has recently been shown empirically that gene conversion can homogenize such repeats, resulting in longer stretches of absolute identity that may increase the rate of non-allelic homologous recombination.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 30 publications
1
17
0
Order By: Relevance
“…These estimates are in good agreement with previous calculations of the IGC rate in the human genome [10], [62], [68], but several orders of magnitude higher than per site rates of non-allelic crossing over [69], [70]. Our analysis surveyed 38.9 Mb (19.45 Mb duplicated sequence), suggesting that ∼60 sites are converted via gene conversion per individual per generation.…”
Section: Resultssupporting
confidence: 91%
“…These estimates are in good agreement with previous calculations of the IGC rate in the human genome [10], [62], [68], but several orders of magnitude higher than per site rates of non-allelic crossing over [69], [70]. Our analysis surveyed 38.9 Mb (19.45 Mb duplicated sequence), suggesting that ∼60 sites are converted via gene conversion per individual per generation.…”
Section: Resultssupporting
confidence: 91%
“…First, segmental duplications are known to be associated with SVs genome-wide 42 , and second, duplications have been shown specifically to facilitate structural variation in IGH 7 . Segmental duplications and tandem repeats also mediate sequence exchange either through gene conversion or recombination, that can either result in the homogenization of paralogous sequences 29,30,43 , or in an increase in genetic diversity 44,45 . Illustrating the latter of these two scenarios, we found that for IGHV, SNP density was highest in regions including segmental duplications, particularly those with >95% sequence identity with their paralogs; similar trends were not noted for SNP density estimates calculated within non-SD repeat regions (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A gene conversion event, on the other hand, inherently homogenizes a region or a ''tract'' of duplicate genes because a tract of a ''donor'' gene overwrites a homologous region of an ''acceptor'' gene. This generally results in a ''patchy'' pattern of regional phylogenetic signals where short tracts of type II informative sites are dispersed in the background of type I informative sites (Kawamura et al 1992;Kitano and Saitou 1999;Hurles 2001;Winter and Ponting 2005; fig. 7B).…”
Section: Human-macaquementioning
confidence: 99%